-3(x-8)+6=-72

Simple and best practice solution for -3(x-8)+6=-72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-8)+6=-72 equation:


Simplifying
-3(x + -8) + 6 = -72

Reorder the terms:
-3(-8 + x) + 6 = -72
(-8 * -3 + x * -3) + 6 = -72
(24 + -3x) + 6 = -72

Reorder the terms:
24 + 6 + -3x = -72

Combine like terms: 24 + 6 = 30
30 + -3x = -72

Solving
30 + -3x = -72

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -3x = -72 + -30

Combine like terms: 30 + -30 = 0
0 + -3x = -72 + -30
-3x = -72 + -30

Combine like terms: -72 + -30 = -102
-3x = -102

Divide each side by '-3'.
x = 34

Simplifying
x = 34

See similar equations:

| 4x+3=3+x+-3x | | 2n+14n+2=-30 | | -3(y-3)=-2(4-2y) | | 3b+17-1+b-4(4)=100-4 | | x^3(dy/dx)=y^2(x-4) | | 1/2(13-6x)=7(-2x-4) | | -w/20=-2.2 | | x(x-2)+2=0 | | 4(d+3)-3(d-4)+5(d+6)=96 | | M+3m=102ft | | (0)-4x=-2 | | k-5=5k+7 | | 3k=2-k | | -3(g-4+6)+5=8 | | -4.9x^2+10x+40=0 | | (6x)-14=x+7 | | -4.9x^2+10t+40=0 | | 6x-14=x+7 | | 82=1.125c+32 | | X-(12-x)=20 | | y^2-62+2y-5+2y-5=180 | | 3+(7+6-9)= | | x^2-2x-37=-5 | | 12(xy-2)+2xy=18 | | 7x-8=125 | | x^2-2x-35=-5 | | 15-x=-76 | | 2=y-4x | | x=y+34 | | g-3/7=2/7 | | 5n+34+2(1-7n)=10 | | M*3m=102ft |

Equations solver categories